2023
DOI: 10.3390/healthcare11040593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geriatric Admissions on Workload in the Emergency Department

Abstract: Background: Due to the increase in life expectancy, both the general population and the population of patients of emergency departments (ED) are getting older. An understanding of differences, workload and resource requirements may be helpful in improving patient care. The main goal of this study was to evaluate the reasons for geriatric admissions in the ED, identify typical medical problems and assess the number of resources in order to provide more effective management. Methods: We examined 35,720 elderly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Conditions like delirium or electrolyte disbalance may provoke altered mental status that may be interpreted as a sign of a vascular incident. This group also is at risk of prolonged LOS and requires more ED resources [23]. Other authors also reported increased LOS During the pandemic, EDs were the first line of action and were the most heavily burdened.…”
Section: Resultsmentioning
confidence: 96%
“…Conditions like delirium or electrolyte disbalance may provoke altered mental status that may be interpreted as a sign of a vascular incident. This group also is at risk of prolonged LOS and requires more ED resources [23]. Other authors also reported increased LOS During the pandemic, EDs were the first line of action and were the most heavily burdened.…”
Section: Resultsmentioning
confidence: 96%
“…EDs, however, are hardly ever structured to effectively manage the multidimensional complexity of geriatric patients [2,3], in whom acute diseases or exacerbations of chronic illnesses often exhibit atypical presentations and overlapping clinical pictures [4]. This may lead to diagnostic delays, long ED boarding times, inappropriate hospitalizations, and, ultimately, poor outcomes, including increased risk of delirium and hospital-related infection, loss of independence, and mortality [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia encountered in the emergency department (ED), constituting a substantial proportion of total ED admissions, ranging from 3.3% to 10% and currently ranking as a primary cause for geriatric visits [ 1 , 2 , 3 ]. Its pervasive prevalence is on the ascent, a consequence attributed to societal lifestyle changes, which, in turn, contribute to an increase in associated diseases and symptoms [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%